Bursaphelenchus obeche sp. n. (Nematoda: Parasitaphelenchidae) found in packaging wood exported from Indonesia to Ningbo, China (Journal of Nematode Morphology and Systematics, 2010)
Bursaphelenchus obeche sp. n. isolated from packaging wood made of Triplochiton scleroxylon and imported from Indonesia to China is described. It is characterized by its body 810 (668-918) μm and 916 (801-1069) μm long for males and females, respectively; slim body (a = 37 and 34, respectively); stylet 15 μm long; lateral field with four lines; mean value of vulva position 75%; a vulval flap seen in lateral view; length of post-uterine branch about three-fourths of vulva-anus  distance; female tail long and conical (c=16), tapering to a rounded terminus, and its posterior region hook-like; male spicules 23 μm long, cross-striped in their central part, and  having compact capitulum with broad rostrum which has a finely rounded or pointed tip; male tail terminus with distinct bursa seen in dorso-ventral position; three pairs of ventrosublateral papillae (one adanal pair, and two postanal pairs at the  beginning of the bursa and adjacent to each other) and a single preanal papilla present. The new species belongs to the ‘africanus’ group of the genus Bursaphelenchus and is most similar to B. africanus and B. burgermeisteri, from which it can be distinguished as well as from other Bursaphelenchus species by morphology, ITS-RFLP patterns and sequencing results.